The CoCoS trial: Caloric Control in Cardiac Surgery patients promotes survival, an interventional trial with retrospective control. Issue 3 (June 2018) - De Waele, Elisabeth; Nguyen, Ducnam; De Bondt, Karlien; La Meir, Mark; Diltoer, Marc; Honoré, Patrick M.; Spapen, Herbert; Pen, Joeri J.
Summary: Background & aims: Malnutrition is widespread among cardiac surgery patients and is independently related to an adverse postoperative evolution or outcome. We aimed to assess whether nutrition therapy (NT) could alter caloric deficit, morbidity, and mortality in patients scheduled for non-emergency coronary artery bypass graft (CABG) or aortic valve surgery. Methods: 351 patients undergoing either elective CABG or aortic valve surgery were studied. Patients receiving NT were enrolled from January 2013 until December 2014. A retrospective control group (CT) consisted of 142 matched patients. The primary endpoint was to evaluate whether NT could limit caloric deficit (Intake to Need Deviation). Secondary endpoints addressed the potential effect of NT on morbidity and mortality. Patients were followed for one year after surgery. Results: There was no significant difference in patient, laboratory or mortality profile between the groups. Caloric deficit could be limited in the intervention group, essentially by providing oral feeding and oral supplements. A minority of patients required enteral or parenteral nutrition during their hospital stay. Caloric deficit increased after the second postoperative day because more patients were switched to oral feeding and intravenous infusions were omitted. Combining CABG and aortic valve surgery, male patients in the NT group had significantly less arrhythmia than in the CT group (7% versus 31%; P = 0.0056), while females in the NT group had significantly less pneumonia than in the CT group (7% versus 22%; P = 0.0183). Survival was significantly higher in female NT patients compared to CT patients, both for CABG (100% versus 83%; P = 0.0015) and aortic valve surgery (97% versus 78%; P = 0.0337). Conclusion: The results suggest that NT beneficially affects morbidity and mortality in elective cardiac surgery patients. The impact of NT seems more pronounced in women than in men. Registration: Clinicaltrials.gov: NCT02902341 .